Quercetin and fisetin enhanced the small intestine cellular uptake and plasma levels of epi-catechins in in vitro and in vivo models. Issue 1 (23rd November 2017) - Chung, Jin-Oh; Lee, Seon-Bong; Jeong, Kang-Hyun; Song, Ji-Hoon; Kim, Su-Kyung; Joo, Kyung-Mi; Jeong, Hyun-Woo; Choi, Jin-Kyu; Kim, Jeong-Kee; Kim, Wan-Gi; Shin, Song-Seok; Shim, Soon-Mi
Abstract : The catechol-containing flavonoids quercetin and fisetin could positively affect the absorption of catechins due to their strong affinity for COMT, which can methylate and cause the excretion of catechins. Abstract : Quercetin and fisetin, known as catechol-containing flavonoids, could positively affect the absorption of catechins due to their strong affinity for catechol- O -methyl transferase (COMT), which can methylate and cause the excretion of catechins. The current study examined the effect of quercetin and fisetin on the absorption of epi -catechins (ECs) by using a Caco-2 cell line and an in vivo model. The intestinal transport of total catechins by Caco-2 cells was enhanced from 1.3- to 1.6-fold and 1.4- to 1.7-fold by adding quercetin and fisetin, respectively, compared to the control. It was even higher in the treatment with a mixture of quercetin and fisetin. While EC had the highest value of intestinal transport (169% of the control) in 10% quercetin treatment, EGC (235%), EGCG (244%), and ECG (242%) were significantly transported in the treatment with a 5% mixture of quercetin and fisetin ( p < 0.05). In an in vivo pharmacokinetic study, the values of the area under the plasma concentration–time curve (AUC, ng h mL −1 ) were also higher in rats orally administered EGCG with 10% quercetin (365.5 ± 25.5) or 10% fisetin (825.3 ± 46.7) than in those administered EGCG only (111.3 ± 13.1). Methylated quercetin and methylated fisetin were determined to be m / z 317.24 and m / z 301.25 [M + H] + with their own product ions, respectively. The results indicate that quercetin or fisetin is superior to ECs for methylation by COMT.